1997
DOI: 10.1016/s1350-4177(97)00023-0
|View full text |Cite
|
Sign up to set email alerts
|

Sonication of aqueous solutions of chlorobenzene

Abstract: Sonication at two frequencies (20 and 900 kHz) was carried out on dilute (220 ppm) aqueous solutions of chlorobenzene. The formation of chloride ions was followed using ion chromatography. The solutions became more colored with time; the absorbance maximum was around 270 nm. Some of the compounds remaining in the solution could be identified; they were chlorinated phenols, chloronaphthalene, mono and dichlorobiphenyls, etc. At the same acoustic power, the rate of chloride formation with 20 kHz ultrasound was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…This saturation has been observed in several systems [87,88,89]. Other authors have pointed out that lower intensities are more effective than higher intensities at the same total power, not only in experiments on water sonolysis [90] but also in degradation process of chlorinated organocompounds [45].…”
Section: Influence Of the Ultrasonic Powermentioning
confidence: 74%
See 4 more Smart Citations
“…This saturation has been observed in several systems [87,88,89]. Other authors have pointed out that lower intensities are more effective than higher intensities at the same total power, not only in experiments on water sonolysis [90] but also in degradation process of chlorinated organocompounds [45].…”
Section: Influence Of the Ultrasonic Powermentioning
confidence: 74%
“…Some controversy is again found in the literature. An increase of the rate of degradation with frequency has been routinely reported for the degradation of volatile compounds such as CCl 4 [34], trichloroethylene [38] and chlorobenzene [45]. However, if the range of studied frequencies reaches values higher than 1 MHz, some authors have detected a maximum around ranging 350-850 kHz [30,36] while other authors have reported a continuous increase [35].…”
Section: Influence Of the Ultrasonic Frequencymentioning
confidence: 96%
See 3 more Smart Citations